3*(cos(t) + t*sin(t))
The derivative of a constant times a function is the constant times the derivative of the function.
Differentiate tsin(t)+cos(t)t \sin{\left(t \right)} + \cos{\left(t \right)}tsin(t)+cos(t) term by term:
The derivative of cosine is negative sine:
Apply the product rule:
f(t)=tf{\left(t \right)} = tf(t)=t; to find ddtf(t)\frac{d}{d t} f{\left(t \right)}dtdf(t):
Apply the power rule: ttt goes to 111
g(t)=sin(t)g{\left(t \right)} = \sin{\left(t \right)}g(t)=sin(t); to find ddtg(t)\frac{d}{d t} g{\left(t \right)}dtdg(t):
The derivative of sine is cosine:
The result is: tcos(t)+sin(t)t \cos{\left(t \right)} + \sin{\left(t \right)}tcos(t)+sin(t)
The result is: tcos(t)t \cos{\left(t \right)}tcos(t)
So, the result is: 3tcos(t)3 t \cos{\left(t \right)}3tcos(t)
The answer is:
3*t*cos(t)
3*(-t*sin(t) + cos(t))
-3*(2*sin(t) + t*cos(t))